PENYULUHAN PERIKANAN BIOAKUAPONIK : INTEGRASI SISTEM AKUAKULTUR BERTEKNOLOGI BIOFLOK DENGAN SISTEM HIDROPONIK - Mumpuni, Fia Sri; Muarif; Marhaly, Mulyana; Wahyudin, Yudi; Lesmana, Dudi; Farasfatih, Ekorini; Yulianti, Nani (Universitas Djuanda, 2022)
The purpose of this community service activity is to transfer knowledge about the application and use of bioquaponic technology which is the integration of biofloc technology and hydroponic systems. The target of this community service activity is ornamental fish cultivators and the general public in Ciomas District, Bogor Regency. The activity was carried out in December 2021. The method of community service activities carried out was the lecture method, discussion and demonstration of direct practice in the field. The results of this community service activity in Ciomas Subdistrict, Bogor Regency, show that there is a transfer of knowledge regarding the integration of bioaquaponics, biofloc technology, hydroponic systems, fish disease management, business development and group dynamics as well as demonstrations of the application and use of bioaquaponics. Based on the results of the pre-test and post-test conducted before and after community service, there was an increase in the capacity and capability of the representation of ornamental fish cultivators, which increased by 50 percent on average. The ornamental fish farming business actors who represent the cultivating community in this activity also get new networks to strengthen the collaboration of the ornamental fish cultivator community, business people and universities. Thus, the expected output of activities in community service in Ciomas District, Bogor Regency, namely (i) an increase in knowledge of ornamental fish farmers regarding the integration of aquaculture systems with biofloc technology and aquaponics systems, (ii) increasing the quality and quantity of ornamental fish production, and (iii) an increase in the network of ornamental fish cultivators in Ciomas District, Bogor Regency, can be achieved.